Occupation-centred practice with children : a practical guide for occupational therapists. - Rodger, Sylvia, ....-; Kennedy-Behr, Ann, ....- (West Sussex : John Wiley & Sons, 2017)
Occupation-Centred Practice with Children remains the only occupational therapy book which supports the development and implementation of occupation-centred practice with children. Drawing on the latest occupational therapy theory and research, this new edition has been fully updated throughout, and includes new chapters on occupational transitions for children and young people, assessing children's occupations and participation, intervention within schools, the arts and children's occupational opportunities, as well as using animals to support children's occupational engagement. Key features: Written by an international expert team of contributors. Each chapter begins with preliminary questions to assist with consideration of current knowledge, and then reflection questions at the conclusion to allow revision of key content in order to support independent learning. Highly practical, with a range of case studies, key point summaries, reflective questions, best practice guidelines, and a range of tools, interventions and techniques to aid applications to practice. A new appendix outlining all the assessments referred to in the book has now been included. Occupation-Centred Practice with Children is a practical, theoretically grounded and evidence based guide to contemporary occupational therapy practice, and is important reading for all occupational therapy students and therapists wishing to make a real difference to children and their families' lives.
Keywords: Ergotherapie; Occupational therapy